Development of the Sportife learning model based on sport tourism and science through experiential learning - Stephani Yane; Heri Rustanto; Handi Darmawan; Arinda Eka Lidiastuti; Rio Wardhani (Universitas Muhammadiyah Malang, 2025)
Many students still view physical education merely as physical activity, without understanding the industrial opportunities that can develop from this sector. This study integrates sport tourism viewed not just as economic activity, but as an intensive, performance-oriented context and sport science, which provides the foundational knowledge for optimizing human performance and experience quality within this setting. The study aims to develop the Sportife learning model and assess its validity through expert evaluation to ensure its feasibility for classroom implementation. This study uses the research and development method adopted from the Hannafin and Peck model, which consists of three stages: 1) needs analysis; 2) design phase; 3) implementation phase. In the implementation stage, the model was applied through experimental testing to examine its effectiveness in improving student learning outcomes. The research results produced a prototype of the Sportife learning model development, with a learning implementation response of 85.80% (very strong). The implementation of the model showed a 26.62% increase in students’ understanding of the sports-based creative economy. The Sportife model provides a holistic learning experience, integrating theory and practice of sport tourism, while fostering students’ analytical, creative, and collaborative skills. High acceptance (85.80%) confirms the practicality and relevance of the model in sports-based entrepreneurship learning.